2014
DOI: 10.1177/0972150914543421
|View full text |Cite
|
Sign up to set email alerts
|

Banking Sector Development and Economic Growth in India

Abstract: This article investigates short-run as well as long-run relationships, and also causality relationships between banking sector development and the economic growth of India for which empirical analysis is performed using annual data. We use a new data set of banking sector development indicators to argue that banking sector development substantially affected economic growth. We find strong evidence that banking sector development caused economic growth in the Indian economy, especially in the period between 196… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Similarly, the firm size is also positively associated with firm value, and this is in line with the studies of Rovolis and Feidakis (2014). Further, the association of tangibility and firm value is positive and significant at the one percent level of significance, and this supports the agency cost theory, and is in support to the studies of Rajan and Zingales (1995) and Tripathy and Pradhan (2014). Profitability is negatively associated with the firm value, since the coefficient is significant and negative.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Similarly, the firm size is also positively associated with firm value, and this is in line with the studies of Rovolis and Feidakis (2014). Further, the association of tangibility and firm value is positive and significant at the one percent level of significance, and this supports the agency cost theory, and is in support to the studies of Rajan and Zingales (1995) and Tripathy and Pradhan (2014). Profitability is negatively associated with the firm value, since the coefficient is significant and negative.…”
Section: Resultssupporting
confidence: 84%
“…In general, a positive effect of (past) profitability on efficiency has been expected. More profitable firms are generally better managed and thus are expected to be more efficient (Ebaid, 2009;Saeedi & Mahmoodi, 2011, Tripathy & Pradhan, 2014Frank & Goyal, 2003). On the other hand, leverage measured by long-term debt to stockholders' equity has been considered as the dependent variable.…”
Section: Methodsmentioning
confidence: 99%
“…A survey of literature has shown that existing studies are biased towards the use of money market-based indicators of which domestic credit to the private sector has been used in all existing studies For instance, Shahbaz and Rahman (2012) used the conventional measures of financial development, while Tripathy and Pradhan (2014) limited their measure to banking sector only. However, Yartey and Adjasi (2007) based their study solely on capital market indicators for 19 exchanges in SSA.…”
Section: Methodsmentioning
confidence: 99%
“…The study of Tripathy & Pradhan (2014) analyzed the short-run and long-run relationship, and causal relationships between banking sector development and economic growth of India from 1960 to 2011 that covered 52 years of post-independence for the country. There is strong evidence than development in the banking sector cause economic growth in the economy of India (Tripathy & Pradhan, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%